AKIBAT HUKUM KEPAILITAN PERORANGAN TERHADAP PERSEROAN PERORANGAN - Rahayu, Laili Putri; Saleh, Moh. (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
The aim of this study is to analyze the legal consequences of company bankruptcy for individuals and the legal certainty of company bankruptcy for individuals. The method used in this study is normative juridical with a statutory approach and a conceptual approach. This study uses primary, secondary and tertiary legal materials. Data collection uses document study or literature study techniques. The data that has been obtained is analyzed qualitatively using deductive and inductive methods or interpretation is carried out. The results of the study show that a person who is declared bankrupt in an individual company can apply for cancellation of all forms of legal action against assets to the court before the decision to declare bankruptcy is pronounced. An individual company that has been declared bankrupt through a court decision can immediately give rise to legal consequences, namely the debtor loses the right to carry out management and control over the assets owned and everything produced during bankruptcy, and the rights and obligations of the bankrupt debtor are transferred to the curator to manage and control The rules are as regulated in Article 19 to Article 62 of Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations